Why is $g^e \mod p = g^{e \mod (p-1)} \mod p$ if p is prime. I don't get it. It follows from Fermat's little theorem.


Fermat's little theorem $$a^p \equiv a \pmod{p} \Leftrightarrow a^{p-1} \equiv 1 \pmod{p}(p \nmid a)$$

so next divides $e$ with $p-1$:$$e=(p-1)r+s;$$ $$s\equiv e \pmod{p-1};$$ so we get $$g^{(p-1)r+s} \pmod {p} \equiv (g^{p-1})^rg^s \pmod{p}$$ follow Fermat's little theorem $g^{p-1} \equiv 1\pmod{p}$ finally we get :$$g^{(p-1)r+s} \pmod {p} \equiv (g^{p-1})^rg^s \pmod{p} \equiv g^s \pmod{p}$$ $\Leftrightarrow$ $$g^e \pmod{p} \equiv g^{e \pmod{p-1}} \pmod{p}$$

  • 1
    $\begingroup$ @Alex For the left-to-right implication in the first equivalence to hold true, you should probably add that $p \nmid a$. $\endgroup$ – hakoja Sep 10 '13 at 9:32

Your Answer

By clicking "Post Your Answer", you acknowledge that you have read our updated terms of service, privacy policy and cookie policy, and that your continued use of the website is subject to these policies.

Not the answer you're looking for? Browse other questions tagged or ask your own question.